2005
DOI: 10.1002/gps.1416
|View full text |Cite
|
Sign up to set email alerts
|

The management of inappropriate vocalisation in dementia: a hierarchical approach

Abstract: Interventions for inappropriate vocalisation in dementia are not limited to medication. Environmental factors and behavioural approaches are considered ahead of pharmacotherapy as the concepts of Underlying Illness, Hidden Meaning and Empirical Treatments are used to structure consideration of important, and sometimes overlooked, issues including pain, depression and overall level of stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 37 publications
0
34
0
1
Order By: Relevance
“…The repeated appeal to return home tends to occur during the busiest evening hours in nursing facilities (Barton et al 2005;Zaraa 2003). Care workers prepare residents' tables for supper and shift their work between the day and the night workers.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The repeated appeal to return home tends to occur during the busiest evening hours in nursing facilities (Barton et al 2005;Zaraa 2003). Care workers prepare residents' tables for supper and shift their work between the day and the night workers.…”
Section: Resultsmentioning
confidence: 98%
“…Unfortunately, their experiential learning is often concealed below the level of consciousness: it has not been accumulated as usable knowledge, nor has it been articulated in a way that can be shared with other workers. The approach to BPSD among care workers has been trapped in a "trial and error" type of practice (Barton et al 2005;Clavel 1999;Hutchinson et al 1996;Smith et al 2004) which seldom benefits from the expertise of long-time formal caregivers.…”
Section: Introductionmentioning
confidence: 99%
“…The exact mechanisms inducing vocal agitation are yet unknown [45] but might be explained by interruption of the frontal subcortical circuits [35] . Vocal agitation has also been associated with severe cognitive impairment [46] or severe dementia with total dissolution of speech [35] , depression [47,48] , psychosis [48] , undertreated pain [46,48] or environmental factors such as noise levels or over/understimulation [48,49] . There may be different types of disruptive vocalizations [44] .…”
Section: Discussionmentioning
confidence: 99%
“…Research has demonstrated that BEs often arise from incongruence between a person’s needs (e.g., pain/discomfort 6,7 , loneliness/isolation 8 , boredom 9,10 , sensory deprivation 11,12 ) and the degree to which the environment fulfills these needs 13,14 . Consequently, BEs may indicate unmet needs, an inadequate attempt to fill those needs, or a desire for help.…”
mentioning
confidence: 99%